Wilderness : a novel - Parker, Robert B., 1932-2010. (New York : Delacorte Press/S. Lawrence, 1979)
obert B. Parker was the author of seventy books, including the legendary Spenser detective series, novels featuring Chief Jesse Stone, and the acclaimed Virgil Cole/Everett Hitch westerns, as well as the Sunny Randall novels.
Keywords: Drama; Social; Mystery